Pengembangan PENGEMBANGAN MEDIA AUDIO VISUAL PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Siregar, Fadhil; Harahap, Nova A.; Harahap, Sri K. (Educandumedia: Jurnal Ilmu pendidikan dan kependidikan, 2022)
The type of research used is Research and Development (R&D) which refers to the learning model or design, namely ADDIE which stands for analysis, design, development, implementation, evaluation. The types of data in this study are qualitative and quantitative data. The research instruments used were media and material validation questionnaires, student response questionnaires, and student learning outcomes tests.